Synergistic effect of methane emission through ruminant production (2015)
The world we live in is not in isolation, therefore every action undertaken by humans and animals have a direct effect on humans. Some sort of boomerang effect. Methane is produced mostly by anaerobic microbial metabolism in the rumen and sent out through eructation into the environment. Methane and other gases such as carbon dioxide and nitrous oxide (C02 and N20) have been giving great concern worldwide as they represent greenhouse gases (GHG). Though produced as a result of the actions of methanogens (bacteria) within the rumen, methane gas portend grave consequences through global warming and other negative effects as it relates to interaction between the environment and living things. Hence, this paper discusses the effects of methane, the producers and action of production and mitigation strategies are all reviewed in this study.